Saving Lives: Mapping the Power of LGBTIQ+ First Nations Creative Artists - Sandy O'Sullivan (Social Inclusion, 2021)
In 2020, I was funded by the Australian Research Council to undertake research that examines the ways in which queer Indigenous creative practitioners create impact and influence. With a program titled “Saving Lives: Mapping the Influence of LGBTIQ+ First Nations Creative Artists,” the mapping is currently underway to explore how creativity has been used to demonstrate our reality and potential as queer First Nations’ Peoples. The title of this commentary explicitly reframes this from influence, to one of insistent resistance. It explores beyond how we persuade, to understand why the resistance in the work of First Nations’ queer creatives lays the groundwork for a future where the complexity of our identities are centred, and where young, queer Indigenous people can realise their own imaginings.